NGC 6309, a planetary nebula that shifted from round to multipolar. Issue 2 (21st November 2014) - Rubio, G.; Vázquez, R.; Ramos-Larios, G.; Guerrero, M. A.; Olguín, L.; Guillén, P. F.; Mata, H.
Abstract : We present new narrow-band Hα, [N ii ], and [O iii ] high-resolution images of the quadrupolar planetary nebula NGC 6309 that show in great detail its bipolar lobes and reveal new morphological features. New high- and low-dispersion long-slit spectra have been obtained to help in the investigation of the new nebular components. The images and spectra unveil two diffuse blobs, one of them located ≃55 arcsec from the central star along the NE direction (PA = +71°) and the other at ≃ 78 arcsec in the SW direction (PA = –151°). Therefore, these structures do not share the symmetry axes of the inner bipolar outflows. Their radial velocities relative to the system are quite low: +3 and –4 km s −1, respectively. Spectroscopic data confirm a high [O iii ] to Hβ ratio, indicating that the blobs are being excited by the UV flux from the central star. Our images convincingly show a spherical halo 60 arcsec in diameter encircling the quadrupolar nebula. The expansion velocity of this shell is low, ≤6 km s −1 . To study the formation history of NGC 6309, we have used our new images and spectra, as well as available echelle spectra of the innermost regions, to estimate the kinematical age of each structural component: the software shape has been used to construct a morphokinematic model for the ring and the bipolar flows that implies an age of ∼4000 yr, the expansion of the halo sets a lower limit for its age ≥46 000 yr, and the very low expansion of the blobs suggests they are part of a large structure corresponding to a mass ejection that took place ∼150 000 yr ago. In NGC 6309, we have direct evidence of a change in the geometry of mass-loss, from spherical in the halo to axially symmetric in the two pairs of bipolar lobes.